Tipping the immunostimulatory and inhibitory DAMP balance to harness immunogenic cell death - K. Hayashi (Nature Portfolio, 2020)
Most chemotherapeutic agents, including gemcitabine, do not elicit immunogenic cell death, a phenomenon associated with the release of damage-associated molecule patterns (DAMPs). Here, the authors show that gemcitabine-treated dying cancer cells express hallmark DAMPs but their immunogenic properties are hindered by the concomitant release of the inhibitory DAMP PGE2.